2003
DOI: 10.1073/pnas.1232376100
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant lamination in the cerebral cortex of mouse embryos lacking DNA topoisomerase IIβ

Abstract: We have examined corticogenesis in mouse embryos lacking DNA topoisomerase II␤ (II␤) in the brain or in all tissues. The absence of II␤, a type II DNA topoisomerase normally expressed in postmitotic cells in the developing cortex, severely affects cerebral stratification: no subplate is discernible, and neurons born at later stages of corticogenesis fail to migrate to the superficial layers. This abnormal pattern of neuron positioning in the cerebral cortex is reminiscent of that observed in mouse mutants defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 47 publications
6
115
2
Order By: Relevance
“…In every case, neurite pathfinding to the retinal or tectal neuropil is preserved, and the wild-type laminar pattern is usually approximated, but fine targeting is disrupted. As in the mouse top2b mutant Lyu and Wang, 2003), the earliest steps of developmentproliferation and mitotic exit -are preserved in zebrafish noto mutants. In the mouse Top2b knockout, laminar organization of neuronal cell bodies in the cortex and pathfinding of some motor and sensory axons are also disrupted, suggesting additional defects in neural patterning not seen here in the zebrafish visual system.…”
Section: Discussionmentioning
confidence: 86%
“…In every case, neurite pathfinding to the retinal or tectal neuropil is preserved, and the wild-type laminar pattern is usually approximated, but fine targeting is disrupted. As in the mouse top2b mutant Lyu and Wang, 2003), the earliest steps of developmentproliferation and mitotic exit -are preserved in zebrafish noto mutants. In the mouse Top2b knockout, laminar organization of neuronal cell bodies in the cortex and pathfinding of some motor and sensory axons are also disrupted, suggesting additional defects in neural patterning not seen here in the zebrafish visual system.…”
Section: Discussionmentioning
confidence: 86%
“…Topo II, rather than topo I, is active in post replicative spermatogenic cells that undergo the nucleo-histone nucleo-protamine transition (Roca and Mezquita, 1989). The b-isoform of topo II found in higher eukaryotes is not required for cell proliferation, but involved in the regulation of cell fate (Lyu and Wang, 2003). The topological interconversions of DNA underlying these molecular processes are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The high efficacy of doxorubicin chemotherapy is thought to be due to the highly elevated expression of Top2a in cancer cells. By contrast, Top2h is present in all cells, including postmitotic cells (18,20,22,23). Recent studies have suggested that Top2h may play a role in transcription (24,25).…”
Section: Introductionmentioning
confidence: 99%